From socialization to self-socialization? Exploring the role of digital media in the religious lives of young adults in Ghana, Turkey, and Peru - Moberg, Marcus (Religion, 2019)
Previous research has pointed to the central role of media for the current young adult generation when it comes to finding information about religion, exploring beliefs, and developing a religious identity. This article explores how young adult university students in three different contexts - Ghana, Turkey, and Peru - report using digital media for religious purposes. The article builds on previous research on the role of media in religious socialization and explores the usefulness of the notion of self-socialization in a transnational study. The studied contexts are all shown to differ when it comes to levels of self-reported religiosity and use of media for religious purposes. The article illustrates the independent use of digital media in all contexts and self-socialization taking place on a general level, but also highlights the continuous importance of traditional socialization agents, thus questioning simplistic understandings of the role of media in religious socialization.